1995
DOI: 10.1111/j.1365-2273.1995.tb00057.x
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic screening test for obstructive sleep apnoea

Abstract: Third-octave sound analysis was performed on the snoring sounds of nine subjects with obstructive sleep apnoea (OSA) and 18 with simple snoring. Both groups demonstrated a large low frequency peak in linear sound levels at around 80 Hz. However, the OSA group displayed a substantially larger high frequency sound component. We utilized this fact in the development of an acoustic index (Hawke Index: HI) which describes the ratio between the overall A-weighted and linear sound levels for the recorded snoring soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In keeping with our results, some authors reported that the acoustic characteristics of natural snores of nonapneic/simple snoring subjects and those of patients with OSAS were different. [1][2][3][4] Furthermore, some authors reported that acoustic analysis of snoring sounds is useful for identification of the snoring site. 1,[5][6][7][8][9][10][11] Quinn et al 9 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with our results, some authors reported that the acoustic characteristics of natural snores of nonapneic/simple snoring subjects and those of patients with OSAS were different. [1][2][3][4] Furthermore, some authors reported that acoustic analysis of snoring sounds is useful for identification of the snoring site. 1,[5][6][7][8][9][10][11] Quinn et al 9 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for OSAS diagnosis is conventional polysomnography (PSG). However, recent studies suggest that acoustic characteristics of snoring sound may differ between simple snorers and patients with OSAS 1–4 and may be useful for differentiating between these groups. Some authors suggest that not only differential diagnosis, but also detection of the snoring site can be accomplished by sound analysis 1,5–11 …”
Section: Introductionmentioning
confidence: 99%
“…It was found that the ratio of power above 800 Hz to power below 800 Hz could be used to separate snorers from patients with OSA -the OSA snorers had higher frequencies. McCombe et al 43 demonstrated that the OSA group displayed a substantially larger high frequency sound component than the non-OSA group. In another study Herzog et al 44 found that patients with primary snoring revealed peak intensities between 100 and 300 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Sola-Soler et al (2003) studied the differences in spectral envelopes of simple and OSAS snores and suggested the standard deviation of formant frequencies as a criterion for distinction among simple snores and OSAS snores. McCombe et al (1995) introduced a measure of high frequency content (Hawke Index) for screening OSAS.…”
Section: Introductionmentioning
confidence: 99%